The clinical implications of fasting serum insulin levels in patients with insulin-treated type 2 diabetes: a cross-sectional survey - Zhou, Lingli; Luo, Yingying; Wang, Yan; Cheng, Yao; Zhang, Rui; Zhang, Simin; Gong, Siqian; Han, Xueyao; Ji, Linong (Frontiers in Clinical Diabetes and Healthcare, 2023)
Objective This study aims to investigate the clinical implications of fasting insulin levels (Fins) in subjects with type 2 diabetes on insulin therapy. Methods 1553 subjects with type 2 diabetes (774 subjects who never received insulin treatment [N-INS] and 779 subjects who have been receiving insulin therapy [constant insulin treatment, C-INS]) admitted to the department of endocrinology and metabolism were consecutively enrolled in this study. Fins levels were measured and hyperinsulinemia were identified. The underlying mechanisms of hyperinsulinemia were revealed by measuring insulin antibodies (IAs) and analyzing changes of Fins levels before and after PEG precipitation. And the clinical characteristics of patients with different types of hyperinsulinemia were compared. Results Higher Fins levels and incidence (43.8%, 341/779) of hyperinsulinemia (Fins15IU/ml) were observed in patients with C-INS than patients with N-INS. Among subjects with C-INS and hyperinsulinemia, 66.9% (228/341) subjects were IAs positive, and the incidence of IAs was found to be positively associated Fins levels. By performing PEG precipitation, we found that all the subjects without IAs (Real hyperinsulinemia), and 31.1% subjects (71/228) with IAs remained hyperinsulinemia (Real and IAs-related hyperinsulinemia) after PEG precipitation, while Fins levels in the other 68.9% subjects (157/228) with IAs were turned down to normal levels (IAs-related hyperinsulinemia) after PEG precipitation. Comparisons between groups showed patients with real hyperinsulinemia showed more obvious insulin resistance characteristics, including higher lipid levels, BMI and HOMA2-IR, higher incidence of hypertension, obesity and metabolic syndrome (p<0.05). While the risk of hypoglycemia and glucose variability increased significantly in subjects with IAs compared with those without IAs. A cutoff of Fins/C-Peptide ratio (9.3IU/ng), could be used to screen IAs in clinical practice with 83.3% sensitivity and 70% specificity. Conclusions It is necessary to measure Fins in subjects with C-INS to distinguish different types of hyperinsulinemia, which would help to tailor treatment regimens.